TIPOGRAFI DEKORATIF KAWUNG FLORAL REGULAR - Handriyotopo, Handriyotopo (Acintya, 2014)
Typeface as a print advertising communication element has an important role to convey the message.There are many variations in the use of type application in typography. One is a kind of decorativetypeface. The existence of decorative letters during the Dutch East Indies in terms of silografi iswidely used in newspapers. Currently the use of decorative letters is less productive because it is onlyused as a supplement and as an aesthetic element. The creation of works of decorative letters will adddigital reference letters in adopting elements of local culture in the motif. The chosen motif to thesource of creation decorative letters is like motif kawung of Surakarta and Yogyakarta batik stylesthat have a common history. The application of this new type of decorative fonts as supporting visualaesthetic in design wedding invitations, especially themed Javanese batik or marriage. The method ofcreation is through the stages of observation and exploration, experimentation, creation and applicationin the design of wedding invitation cards.Keywords: Decorative letter, batik, wedding invitations